Analisis Gangguan Fungsi Paru pada Pekerja di Area Stockpile Pelabuhan Talang Duku Jambi Tahun 2024 - Fahrandis, Azurly Difi; Yenni, Melda; Entianopa, Entianopa (National Journal of Occupational Health and Safety, 2025)
The International Labour Organization (ILO) reported in 2018 that 2.78 million workers die annually due to occupational accidents and work-related diseases. Approximately 2.4 million (86.3%) of these deaths are caused by work-related illnesses. Dust exposure in the work environment can lead to lung function disorders in workers. This study aims to analyze lung function disorders and their relationship with risk factors among workers in the Stockpile Area of Talang Duku Port, Jambi, in 2024. The research method is cross-sectional, with a sample of 38 workers using research instruments including spirometry, questionnaires, interviews, and observations. Results show that 84.2% of respondents experienced restrictive lung function disorders. There is a significant relationship between the use of PPE (masks) and lung function disorders (p=0.014), but no significant relationship was found with other risk factors. The majority of respondents had attended training (89.5%), had good knowledge (86.8%), normal nutritional status (55.3%), and were active smokers (71.1%). Only 13.2% of respondents always used masks. It is concluded that consistent use of PPE plays an important role in preventing lung function disorders. Efforts are needed to increase awareness and compliance with PPE use, as well as the implementation of a comprehensive occupational health program. Keywords: lung function disorders, stockpile area, PPE, occupational health.